Seasonal activity of cambium and changes in bark structure of hevea brasiliensis - Thomas V; Nair R B; Sailajadevi T; Saraswathyamma C K; Shankar S (Indian Journal of Natural Rubber Research, 2002)
Seasonal activity of vascular cambium and bark anatomical parameters related to latex yield such as thickness of soft bark, latex vessel rows, height and width of ray cells in Hevea brasiliensis were studied for two consecutive annual cycles. Climatic variations have significant influence on cambial rhythm. With the onset of rain in April-May, the cambium started to divide periclinally to produce daughter cells, which differentiated into secondary vascular tissues. Mean maximum thickness for the cambial zone was the highest during monsoon (June-September) and least during summer (February-May). Bark thickness was high during July to October and low during February to May. The number of latex vessels rows in the soft bark was higher during the monsoon season and declined gradually in the succeeding months to a considerably lower number during the summer. While ray height showed significant variation between seasons, width did not. Starch grains varied considerably both in size and distribution in bark, cambium and wood width seasonal fluctuations and were not located in the soft bark during January to March. Calcium oxalate crystals were found throughout the year in the bark with abundance in the month of June, November and February. Depletion of crystals was noticed in August, January and May. The role of reserve metabolities and especially that of crystals in plant metabolism is discussed.
Keywords: Calcium oxalate crystals; Calcium oxalate crystals; Hevea brasiliensis; Hevea brasiliensis; Latex vessels; Latex vessels; Seasonal cambial activity; Seasonal cambial activity; Starch; Starch; Vascular ray; Vascular ray